Review of the genera Paulomanus Young, 1952 and Beamerana Young, 1952 (Hemiptera: Cicadellidae: Typhlocybinae: Empoascini) with description of a new species from Argentina - Catalano, María Inés; Paradell, Susana L.; Dietrich, Christopher H. (Zootaxa, 2014)
The Neotropical microleafhopper genera Paulomanus and Beamerana are redescribed based on study of type material and newly collected specimens. Paulomanus is recorded for the first time from Argentina and a new species, P. falciformis n. sp., is described. Detailed morphological description and illustration of the new species and a key to males of the known species of Paulomanus are provided. A key to genera of the New World Empoascini is also provided.